2019
DOI: 10.1002/aur.2214
|View full text |Cite
|
Sign up to set email alerts
|

Getting Off to a Shaky Start: Specificity in Planning and Feedforward Control During Sensorimotor Learning in Autism Spectrum Disorder

Abstract: Whilst autistic individuals develop new internal action models during sensorimotor learning, the acquired movements are executed less accurately and with greater variability. Such movement profiles are related to differences in sensorimotor integration and/or altered feedforward/feedback sensorimotor control. We investigated the processes underlying sensorimotor learning in autism by quantifying accuracy and variability, relative timing, and feedforward and feedback control. Although autistic individuals demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 75 publications
3
10
0
2
Order By: Relevance
“…This occurs under conditions of full visual feedback and, to a lesser extent, when vision is eliminated upon movement initiation (Glazebrook et al 2009). These latter findings indicate that feedback-based corrective processes are operational in autistic individuals (Mosconi et al 2015) 5 , and we have shown recently that reductions in spatial variability at peak acceleration and peak velocity occur following a relatively short period of sensorimotor training (Foster et al 2020a(Foster et al , 2020b.…”
Section: Insights On Limb Control From Various Special Populations 14mentioning
confidence: 56%
See 2 more Smart Citations
“…This occurs under conditions of full visual feedback and, to a lesser extent, when vision is eliminated upon movement initiation (Glazebrook et al 2009). These latter findings indicate that feedback-based corrective processes are operational in autistic individuals (Mosconi et al 2015) 5 , and we have shown recently that reductions in spatial variability at peak acceleration and peak velocity occur following a relatively short period of sensorimotor training (Foster et al 2020a(Foster et al , 2020b.…”
Section: Insights On Limb Control From Various Special Populations 14mentioning
confidence: 56%
“…4 Given the evidence points toward specificity in autistic sensorimotor control processing, we suggest that kinematic examination of the underlying sensorimotor control and learning processes offers an important route for understanding part of the behavioral autism phenotype. Based on the feedforward and feedback processing systems associated with the multiple process model (Elliott et al , 2017, we have investigated how autistic internal action models operate as part of a feedforward system that controls action-understanding in social contexts, but also the organization, planning and control of goal-directed movements (Foster et al 2020a(Foster et al , 2020bGlazebrook et al 2006Nazarali et al 2009). For example, although higher-level motor planning processes (i.e., grasp height; see Ansuini et al 2018) are operational in autistic adults Nazarali et al 2009) and children (Ansuini et al 2018), both these groups (Nazarali et al 2009;Rinehart et al 2006) have difficulty generalizing internal action models to new, and unexpected movement goals.…”
Section: Insights On Limb Control From Various Special Populations 14mentioning
confidence: 99%
See 1 more Smart Citation
“…É uma condição clínica do neurodesenvolvimento a qual incide sob mais de 1% da população mundial (ANDERSON et al, 2020;JESUS et al, 2020). Marcada por diversas desordens no desenvolvimento psicomotor, o que interfere na competência de comunicação, no comportamento e na interação interpessoal do indivíduo (LEAL et al, 2017;CARVALHO;SOUSA, 2020;FOSTER et al, 2020).…”
Section: Introductionunclassified
“…。近年来针对自闭症患者的 研究也开始关注其感知觉异常与高级认知功能之 间的关系 (Foster et al, 2019;Hayes et al, 2018;Robertson et al, 2017)…”
unclassified